Assessment of biophysical properties of Haemonchus contortus from different life cycle stages with atomic force microscopy - Costa-Junior, Livio M.; Silva, Carolina R.; Soares, Alexandra M. S.; Menezes, Alan S.; Silva, Maria R. L. [UNESP]; Amarante, Alessandro F. T. [UNESP]; Costa, Erivelton F.; Alencar, Luciana M. R. (Elsevier B.V., 2020)
Atomic force microscopy (AFM) was used in this work to investigate the ultrastructural and mechanical characteristics of Haemonchus contortus, the major gastrointestinal nematode that infects small ruminants worldwide. The biophysical characterization of this species is extremely important in order to reveal mechanisms of action of drugs and to classify its ultrastructure and biomechanical properties. High-resolution topographic images by AFM as well as data on biomechanical properties of cuticles were obtained at different stages of H. contortus. The results reveal details of the mechanical and structural properties of this nematode never observed before for nematodes parasite with other microscope techniques. Qualitative and quantitative reductions in the elasticity of the larvae stage egg were compared with those of the morulae stage, and the increased adhesion of unsheathed L(3 )were compared with the same stage of sheathed larvae. The results presented here open possibilities for understanding the mechanisms of drug and biomolecular actions that can be used to control infections caused by H. contortus.
Keywords: Haemonchus contortus; AFM ultramicrography; Biomechanics